Multifunctional systems based on nano-in-microparticles as strategies for drug delivery: advances, challenges, and future perspectives - Carvalho, Suzana Gonçalves [UNESP]; dos Santos, Aline Martins [UNESP]; Polli Silvestre, Amanda Letícia [UNESP]; Tavares, Alberto Gomes [UNESP]; Chorilli, Marlus [UNESP]; Daflon Gremião, Maria Palmira [UNESP] (Taylor & Francis, 2023)
Introduction: Innovative delivery systems are a promising and attractive approach for drug targeting in pharmaceutical technology. Among the various drug delivery systems studied, the association of strategies based on nanoparticles and microparticles, called nano-in-microparticles, has been gaining prominence as it allows targeting in a specific and personalized way, considering the physiological barriers faced in each disease. Areas covered: This review proposes to discuss nano-in-micro systems, updated progress on the main biomaterials used in the preparation of these systems, preparation techniques, physiological considerations, applications and challenges, and possible strategies for drug administration. Finally, we bring future perspectives for advances in clinical and field translation of multifunctional systems based on nano-in-microparticles. Expert opinion: This article brings a new approach to exploring the use of multifunctional systems based on nano-in-microparticles for different applications, in addition, it also emphasizes the use of biomaterials in these systems and their limitations. There is currently no study in the literature that explores this approach, making a review article necessary to address this association of strategies for application in pharmaceutical technology.
Keywords: Biomaterials; drug delivery system; microencapsulation; nanotechnology; polymers